Antimicrobial resistance and rational prescription practices: knowledge, perceptions and confidence of health profession interns in Uganda - Nabidda, Shamim; Ssennyonjo, Rogers; Atwaru, Joseph; Kanyike, Andrew Marvin; Baryayaka, Shiellah; Pangholi, Kennedy; Tusiimire, Jonans (JAC-Antimicrobial Resistance, 2023)
Background: Antimicrobial resistance (AMR) is significantly driven by misuse and overuse of antibiotics. Graduate health profession interns often prescribe antimicrobials under minimum supervision. Objectives: This study explored the knowledge, perceptions and confidence of health profession interns in Uganda regarding AMR and rational prescription practices. Methods: This was a cross-sectional survey employing quantitative techniques carried out between October and November 2022 at six tertiary hospitals in Uganda. Health profession interns including doctors, nurses, midwives and pharmacists were recruited as study participants. Data were collected using online Kobo toolbox software. Data analysis was performed using STATA (StataCorp) version 16. Bivariate analysis and multivariable logistic regression were performed. P < 0.05 was considered statistically significant. Results: We recruited 281 participants with a mean age of 27 ± 3.8 years, of which few (n = 53; 19%) had good knowledge about AMR and rational prescription. The use of professional organization guidelines as a source of information was significantly associated with good knowledge (adjusted OR = 1.9; 95% CI: 1.0–3.5; P = 0.046). Nurses had the least knowledge compared with doctors and pharmacists. Continuous medical education (99%) and availability of clinical guidelines (98%) were identified as the most helpful intervention to improve knowledge. Most participants were confident about accurately diagnosing infections and sepsis and selecting appropriate antimicrobials. Conclusions: Continuous medical education and availability of clinical and professional organization guidelines should be leveraged to improve the knowledge of AMR and rational prescription among health profession interns. Their high confidence in rational prescription practices should be pivotal to the fight against AMR.
Keywords: Antimicrobial resistance; Rational prescription practices; Graduate health profession interns; Misuse and overuse of antibiotics